Experimental Methods to Assess the Effectiveness of Soil Conditioning with Foam in Fully Weathered Granite - Liming Tao; Zhongtian Chen; Jian Cui; Huiwu Wang; Yong Fang (Advances in Materials Science and Engineering)
The application range of the earth pressure balance (EPB) shield has been expanded due to advances in optimization methods, one of which is the application of foam conditioning. This method is widely used in EPB tunnelling owing to its strong applicability in different hydrological and geological conditions. When applying the foam conditioning method under different circumstances, it is necessary to optimize the conditioning parameters. Therefore, it is necessary to propose a test procedure for evaluating foam properties and the conditioning effect. This paper proposes a procedure to assess foaming agents by the mixing test and microscopic observation of the foam and a procedure that combines the slump test, compression test, and shear test to assess the foam-conditioned soil and determine the optimal parameters of conditioning. The test method is introduced and performed on fully weathered granite from Guangzhou Metro Line 21. The test results demonstrate that the foam injection ratio and pressure and type of the foaming agent all influence the performance of the conditioned soil. Moreover, the suggested conditioning scheme is proposed, and the application of the scheme can improve the tunnelling efficiency.